2018
DOI: 10.3390/cancers10110417
|View full text |Cite
|
Sign up to set email alerts
|

Systemic Anti-Cancer Therapy in Synovial Sarcoma: A Systematic Review

Abstract: Synovial sarcoma (SS) is an aggressive malignancy which accounts for approximately 5–10% of all soft-tissue sarcomas. SS has pathologic and genomic characteristics that define it as a distinct subtype of soft tissue sarcoma (STS). STS subtypes continue to be recognized as distinct entities with specific characteristics, including differential chemo-sensitivity. The objective of this study was to conduct a descriptive review of current data on survival outcomes of systemic anti-cancer therapy specific to SS. A … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(25 citation statements)
references
References 70 publications
(175 reference statements)
1
21
0
1
Order By: Relevance
“…Synovial sarcoma (SS) is an aggressive malignancy of mesenchymal origin, accounting for approximately 8% to 10% of all soft-tissue sarcomas (STS). [1][2][3] SS is marked by the presence of a pathognomonic translocation between chromosomes X and 18, t(X;18)(p11.2;q11.2), 4 and its histological characteristics can be identified including monophasic, biphasic, and poorly differentiated SS. 4 Although SS frequently arises in the extremities, its histological feature is not related to synovial tissue.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synovial sarcoma (SS) is an aggressive malignancy of mesenchymal origin, accounting for approximately 8% to 10% of all soft-tissue sarcomas (STS). [1][2][3] SS is marked by the presence of a pathognomonic translocation between chromosomes X and 18, t(X;18)(p11.2;q11.2), 4 and its histological characteristics can be identified including monophasic, biphasic, and poorly differentiated SS. 4 Although SS frequently arises in the extremities, its histological feature is not related to synovial tissue.…”
Section: Introductionmentioning
confidence: 99%
“…12,13 However, controversy has still existed related to the most effective therapy regimen. 2 Once disease progression or chemo-resistance happened, no appropriate systemic agent is targeting the histologic or genomic characteristics of SS. Therefore, recently, several clinical trials on different approved palliative options have been reported, such as trabectedin, 14 pazopanib, 15 and regorafenib.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study combining two prospective trials has reported that for small, localised disease, a surgery-only approach can be a safe and viable treatment option 16. Additionally, neoadjuvant or adjuvant cytotoxic chemotherapy is the mainstay of treatment in cases of advanced disease5 15 17 with several studies showing improved overall patient survival 18–20. However, due to the relative rarity of this disease and its involvement of paediatric populations, there is limited prospective and randomised data analysing survival outcomes for different treatment options.…”
Section: Discussionmentioning
confidence: 99%
“…Anthracycline-based regimes are the first-line therapy [3,4]. Second-line chemotherapeutic agents for synovial sarcoma include Pazopanib, Trabectedin, and Eribulin [4][5][6][7]. For metastatic cases, chemotherapy is the main treatment [2].…”
Section: Introductionmentioning
confidence: 99%